Distribution theory : with applications in engineering and physics - Teodorescu, P. P.; Kecs, Wilhelm; Toma, Antonela (Weinheim, Germany : Wiley-VCH Verlag GmbH & Co. KGaA, 2013)
In this comprehensive monograph, the authors apply modern mathematical methods to the study of mechanical and physical phenoema or techniques in acoustics, optics, and electrostatics, where classical mathematical tools fail. They present a general method of approaching problems, pointing out different aspects and difficulties that may occur. With respect to the theory of distributions, only the results and the principle theorems are given as well as some mathematical results. The book also systematically deals with a large number of applications to problems of general Newtonian mechanics, as well as to problems pertaining to the mechanics of deformable solids and physics. Special attention is place upon the introduction of corresponding mathematical models. -- P. [4] of cover.
Introduction to the Distribution Theory -- Integral Transforms of Distributions -- Variational Calculus and Differential Equations in Distributions -- Representation in Distributions of Mechanical and Physical Quantities -- Applications of the Distribution Theory in Mechanics -- Applications of the Distribution Theory to the Mechanics of the Linear Elastic Bodies -- Applications of the Distribution Theory of Linear Viscoelastic Bodies -- Applications of the Distribution Theory in Electrical Engineering -- Applications of the Distribution Theory in the Study of Elastic Bars -- Applications of the Distribution Theory in the Study of Viscoelastic Bars -- Applications of the Distribution Theory in Physics.
Includes bibliographical references and index.
Print version record.
Keywords: Theory of distributions (Functional analysis); MATHEMATICS -- Functional Analysis; Theory of distributions (Functional analysis); Electronic books